Bidirectional Human Capital Spillover from ASEAN TKA Inflow and Its Impact on the Digital Transformation of Indonesian MSMEs - Caroline Caroline; Etty Puji Lestari; Any Meilany; Soni Agus Irwandi; Nugroho SB Maria; Siti Sumiati; Suhartono (Universitas Hayam Wuruk Perbanas, 2026)
This study examines the impact of the inflow of ASEAN foreign workers on the digital transformation of Indonesian MSMEs in the period 2015–2026. In light of the rising influx of ASEAN foreign workers, totalling 183,964 individuals in 2024, coupled with the inadequate level of MSME digitalisation at 39.7%, this research is critically necessary to bolster the DEFA 2026 objectives and promote inclusive economic growth. This study aims to quantify the extent, pathways, and consequences of human capital spillovers resulting from the influx of ASEAN foreign workers on the digital transformation of SMEs. The study was conducted using the mixed methods approach, using panel data from 34 provinces (N=408) and using the Fixed Effects Model. The results showed that the entry of ASEAN foreign workers has a positive and significant effect on the digital transformation of SMEs (β₁ = 0.427; p < 0.01) with diminishing returns. This study's originality is attributed to its longitudinal methodology, micro-level emphasis on MSMEs, and the formulation of a knowledge-based spillover governance model in the DEFA era. This study concludes that the influx of ASEAN foreign workers is a vital source of human capital spillover for expediting the inclusive and sustainable digital transformation of MSMEs.